Unsafe Condition and Unsafe Act (UCUA) Reporting System For Johor Port with OTP Authentication - MOSDY, NURSYAHMINA; MOHD FOOZY, CIK FERESA (Applied Information Technology And Computer Science, 2025)
The Johor Port Unsafe Condition and Unsafe Act (UCUA) Reporting System handles the issues of managing safety reports, which are currently handled via paper forms and limited online submissions, resulting in delays and increased safety concerns. The goal of this project is to create a web-based UCUA Reporting System applying the Laravel framework, which will streamline the reporting and tracking processes for port personnel and the Health, Safety, Security, and Environment (HSSE) department. The key components like incident reporting, compliance tracking, and notifications are all part of the system, which was created using structured web application approach. The system incorporates important security features like input validation, role-based access control, user authentication, and encrypted data processing to guarantee safe and dependable operations. By improving efficiency, accountability, security, and data management, this system’s operation enables quicker reactions to safety concerns and better regulatory compliance. It is expected that future advancements like advanced analytics integration and mobile accessibility would enhance Johor Port’s reporting system even more.